Disentangling intra-kinship property rights in land : a contribution of economic ethnography to land economics in Africa - (:unkn) unknown (My University, 2008)
The issue of property rights in land has taken central stage in research in institutional economics regarding developing countries. In the African context, numerous studies have dealt with the individualization and commodification of customary land rights. The issue of intra-family land rights tends however to remain a black box, regarding the content of the bundle of rights and duties, the identification of the right holders and the transfers of rights within the family. Drawing from the insights of institutional economics as well as economic and legal anthropology, this paper presents a conceptual framework to rigorously explore the issue of land rights through an economic ethnography.
Keywords: African Research